(3+x)dy-ydx=0

Simple and best practice solution for (3+x)dy-ydx=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3+x)dy-ydx=0 equation:


Simplifying
(3 + x) * dy + -1ydx = 0

Reorder the terms for easier multiplication:
dy(3 + x) + -1ydx = 0
(3 * dy + x * dy) + -1ydx = 0

Reorder the terms:
(dxy + 3dy) + -1ydx = 0
(dxy + 3dy) + -1ydx = 0

Reorder the terms:
dxy + -1dxy + 3dy = 0

Combine like terms: dxy + -1dxy = 0
0 + 3dy = 0
3dy = 0

Solving
3dy = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Divide each side by '3'.
dy = 0

Simplifying
dy = 0

The solution to this equation could not be determined.

See similar equations:

| (3y^2+2y-6)-(2y-y+2)= | | x^2=1/64 | | F(a+b)=10x-5 | | 6cos(3x)+5=0 | | b=1/4*3.14*x2m | | X^2+y^2+4x+8y+4=0 | | t-3/8=1/4 | | 7x^2+14x-8=0 | | P=x^4+2x^2-8 | | 4sin^2(4x)=2 | | n-1/5=3/5 | | 210=30 | | P(x)=x^4+2x^2-8 | | 16e/9=6e-190 | | c=27n+26 | | 26.50+15x=14.50+.25x | | x/7-4=11 | | 98b^2+98b-16=0 | | lnx+ln(x-2)=ln(x-4) | | (10+2x)=25 | | log(3x)-log(14)=0 | | x-2=-3z+2 | | d/2.5-3.5=1.5 | | 3000=8.121x^2+6.406x+257.8 | | h/3.2-1.6=2.5 | | 7/x^2-5x | | h/7.1-6.5=1.2 | | 22z^4/11z^10 | | b/5-19=11 | | 2/3x-3/8x=-8 | | m/7=42 | | b/1.3-5.4=1.8 |

Equations solver categories